Theistic Evolution: Scientific, Philosophical and Theological Concerns - Larmer, Robert (Filozoficzne Aspekty Genezy, 2022)
In this paper, I explore scientific, philosophical, and theological concerns that arise from adopting theistic evolution understood as claiming that the origin and development of life can be entirely accounted for in terms of the operation of natural causes, without any need to posit direct divine intervention. I argue that theistic evolutionists’ commitment to methodological naturalism and their unjustified rejection of gap arguments suggests that their case is not nearly so strong as they suggest. I further argue that accepting theistic evolution most naturally leads to accepting a monistic physicalist account of the person that is at odds with theism’s understanding of human nature.